Hubungan nilai alam sekitar dan nilai peribadi: satu analisa - Zurina Mahadi,; Sino, Hukil (Universiti Kebangsaan Malaysia, 2006)
This review analyses the possible relationship between environmental values and personal values. This review propose that environmental values are the result of a person’s general set of personal values. Multinational studies shown that environmental value orientation namely egocentric, anthropocentric and ecocentric demonstrated link to the Schwartz theory of personal values. This review summarised the findings that support the hypothesised relationships. Finally, the review draws several conclusions regarding the environmental-personal value relationship in corporating a profound set of environmental value system